2017
DOI: 10.1097/ta.0000000000001562
|View full text |Cite
|
Sign up to set email alerts
|

Less is more? Antibiotic duration and outcomes in Fournier’s gangrene

Abstract: Therapeutic, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…3,4 Despite the aggressive management, previous publications reported various mortality rates ranging from 3.6 to 45%. [5][6][7][8][9][10][11][12][13][14] The diverse mortality not only shows the complicated nature of FG, but also indicates the need for a practical risk-stratification scoring system for first-line physicians and care providers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Despite the aggressive management, previous publications reported various mortality rates ranging from 3.6 to 45%. [5][6][7][8][9][10][11][12][13][14] The diverse mortality not only shows the complicated nature of FG, but also indicates the need for a practical risk-stratification scoring system for first-line physicians and care providers.…”
Section: Introductionmentioning
confidence: 99%
“…This fulminant disease can be fatal, and should be regarded as a urological emergency that necessitates broad‐spectrum antimicrobial therapy, intensive care and early surgical intervention . Despite the aggressive management, previous publications reported various mortality rates ranging from 3.6 to 45% . The diverse mortality not only shows the complicated nature of FG, but also indicates the need for a practical risk‐stratification scoring system for first‐line physicians and care providers.…”
Section: Introductionmentioning
confidence: 99%
“…For empirical antibiotic therapy, regimens such as glycopeptides or linezolid with broad-spectrum antibiotics such as carbapenems or piperacillin/tazobactam are recommended; clindamycin in combination with penicillin is recommended for monomicrobial NF caused by group A streptococci [20] . Antibiotic treatment must continue until the patient requires no further debridement and shows hemodynamic recovery, and this duration must be determined for each patient based on their individual circumstances [21] . Treatment durations varied among our patients, with antibiotherapy ranging from as short as nine days to as long as 68 days.…”
Section: Discussionmentioning
confidence: 99%
“…Length of antibiotic duration varies widely as there are no clear guidelines on management. One study compared outcomes in patients who received antibiotics for a scheduled number of days versus patients who stopped receiving antibiotics following surgical debridement and normalization of clinical indicators of infection and found that there was no significant difference in recurrence of infection [ 5 ].…”
Section: Discussionmentioning
confidence: 99%